RfLoc: A Reflector-Assisted Indoor Localization System Using a Single-Antenna AP - Liu, Kaikai; Tian, Zengshan; Li, Ze; Zhou, Mu (IEEE transactions on instrumentation and measurement, 2021)
Could we use a single access point (AP) or even an AP equipped with only a single antenna to provide high-accuracy localization service comparable to that of advanced systems using multiple APs or antenna arrays in indoor environments? To answer this question, we present RfLoc, a novel indoor localization system that enables submeter localization accuracy using a single-antenna AP in this article. To this end, RfLoc introduces a custom-designed active reflector with a simple circuit, which can create reflection paths to assist localization. Since our system does not require time synchronization between the target and AP, the absolute time-of-flight (ToF) is unavailable for localization. Instead, we use the relative ToF among the paths that are close to the ground truth to localize the target. The insight behind RfLoc is to use the designed reflector to create paths in a controllable manner, including the control of their strength and propagation delay. The created paths thus are remarkable in multipath-rich environments and can always be used for localization. Then, we employ a sparse recovery-based method, the orthogonal matching pursuit (OMP), to accurately estimate these path ToFs. With ToF estimates, the proposed two-step target localization algorithm is used to solve the target location, including coarse localization based on the semidefinite programming (SDP) and refined localization based on the least squares (LS). We prototype RfLoc using a software-defined radio platform with orthogonal frequency division multiplexing (OFDM) signal, which incorporates a standard WiFi baseband operating. Extensive experimental results show that it can achieve a median localization accuracy of 0.74 m with 100-MHz signal bandwidth. With the advantage of high localization accuracy and easy deployment, RfLoc could enable many Internet-of-Things (IoT) applications.